Delays in Returning Medical Records: A Factor Analysis: Penundaan dalam Pengembalian Rekam Medis: Analisis Faktor - Azizah, Candra Nur; Yuliani, Resta Dwi (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Medical records are a critical component of hospital administration, ensuring accuracy, completeness, reliability, validity, and timeliness for quality healthcare services. Specific Background: However, delays in returning medical record files remain a challenge in inpatient care, disrupting service standards and continuity of care. Knowledge Gap: Limited research has systematically analyzed delay factors using a structured framework in the Indonesian hospital setting. Aim: This study aims to analyze the factors contributing to delays in returning medical record files at Wahidin Sudiro Husodo Hospital using the 5M framework (man, method, machine, material, money). Results: Findings revealed human factors such as high school-level education, limited knowledge, and lack of training; methodological issues where standard operating procedures for inpatient care were not aligned with the 2x24 hours service standard; material shortcomings due to the absence of a tracer; machine factors showing only the use of an expedition book; and financial factors with no incentive or sanction mechanisms. Novelty: This research provides a comprehensive factor-based analysis of medical record return delays by integrating the 5M approach. Implications: The results highlight the need for policy improvements, targeted training, and structured monitoring to achieve timely and reliable medical record management.Highlights: Delays linked to human, procedural, and infrastructural gaps Application of the 5M framework in hospital record analysis Emphasis on policy reform and staff training for improvement Keywords: Delays, Inpatient, Medical Record, Hospital Administration, 5M Framework